THE EFFECTIVENESS OF SHORT PASS TRAINING WITH SMALL GOALS ON THE PASSING ACCURACY OF STUDENTS AGED 10 TO 12 - Sitompul, Surya Rezeki; Sitompul, Indra Buhanudin (Jurnal Penjaskesrek, 2025)
The aim of this study is to investigate the extent to which training in short passes affects the basic technique of passing in soccer. The observation results show that the 10- to 12-year-old students at the Putra Ciledug soccer school (SSB) still frequently make mistakes when passing, which manifests itself in inaccurate passes, a lack of precision in execution, and passes that are too fast for their teammates to receive. The research method used was an experiment with a one-group pretest-posttest design. The sample in this study consisted of 26 students, using a saturated sampling approach to determine the sample. The research period consisted of 12 sessions, comprising 1 pretest, 10 treatments, and 1 posttest. The data collection instrument used was the low ball passing test by Subagyo Irianto (1995), which has a validity of 0.812 and a reliability of 0.856. Data analysis was performed using a t-test at a significance level of 5%. The results of the study show a significant difference between the pre-test and post-test results (t_calculated = 8.705 > t_table = 1.706; p = 0.021 < 0.05) with a percentage increase of 37.69%. Based on these results, it can be concluded that training short passes with small goals has a significant impact on improving the passing accuracy of 10- to 12-year-old students at SSB Putra Ciledug.